Russian politics the struggle for a new order - Nogee, Joseph L. (1996)
This book offers an up-to-date treatment of Russian politics in the post-Cold War era, drawn from English language and Russian sources. The authors see great potential in recent political developments in the former Soviet Union, and in this book convey the sense of drama embodied in those changes and their impact upon the Russian people. This book focuses on presenting and analyzing long-term factors, rather than simply recounting transitory events-to make this book as useful tomorrow as it is today.